PENERAPAN MULTIMEDIA BERBASIS PERANGKAT LUNAK ONLINE PREZI UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBUATAN PCB BERBANTUAN KOMPUTER DI SMKN 12 BANDUNG - Nugraha, Nara Wityarna (2013)
Hasil penelitian menunjukkan adanya peningkatan nilai hasil dalam pembelajaran menggunakan multimedia berbasis perangkat lunak online prezi ini hasilnya positif. Dari hasil angket siswa menunjukan tingkat tercapaiannya media sebesar 82,4 % dengan kualifikasi baik. Sedangkan dilihat dari hasil nilai gain sebesar 0,40 berkategori sedang, sedangkan peningkatan gain memiliki persentase 80% dengan nilai rata rata posttest sebesar 78,67. Dari hasil penelitian tersebut, dapat disimpulkan bahwa penggunaan multimedia bebasis perangkat lunak online prezi mampu meningkatkan hasil belajar siswa yang terukur dengan peningkatan gain pada hasil pretest-posttest serta mampu meningkatkan minat belajar siswa terhadap mata pelajaran pembuatan PCB berbantuan komputer berdasarkan hasil angket siswa dengan kualifikasi baik. Kata Kunci : Research and Development (R&D), Multimedia, Perangkat lunak online prezi Abstract This study uses research development (research and development / R&D ) undertaken in class X and class XI EPU EPU 2 1 SMKN 12 Bandung . The goal is to determine the improvement of learning outcomes in the use of multimedia -based online software Prezi as a learning medium of computer -aided manufacture of PCB. The initial phase of the study media in due diligence beforehand by some experts who kompeten.Hasil feasibility test in this case using a questionnaire shows the feasibility test value of 82% with a good level of achievement of qualifications so that the media does not need to be revised . After due diligence , the media could be tested on a limited basis to students of class XI Epu 1 SMK Negeri 12 Bandung. The results showed an increase in the value of the learning outcomes in the use of multimedia -based online software Prezi is a positive result . From the student questionnaire results showed levels of 82.4 % tercapaiannya media with good qualifications . While the views of the results of the gain value of 0.40 being categorized , while the percentage increase in the gain has a value of 80 % with an average of 78.67 posttest. From these results , it can be concluded that the use of multimedia software online Prezi bebasis able to improve student learning outcomes measured by an increase in the gain on the pretest-posttest results and can improve students' interest in learning subjects PCB making computer-assisted questionnaire based on the results of students with good qualifications . Keyword : Research and Development (R&D), Multimedia, software prezi online